Migration of Central Venous Catheters in Neonates: A Radiographic Assessment - Gupta, Ruby; Drendel, Amy L.; Hoffmann, Raymond G.; Quijano, Carla V.; Uhing, Michael R. (American Journal of Perinatology, 2016)
Objective This study aims to determine the frequency that umbilical venous catheters (UVCs) and peripherally inserted central catheters (PICCs) migrate into the cardiothymic silhouette after initial verification of correct placement.Study Design This is a single-center, retrospective study in neonates in whom a PICC or UVC was placed. The frequency of catheter tip migration into the cardiothymic silhouette requiring catheter manipulation was determined radiographically at 1 and 24 hours, respectively, after insertion.Results At 1 and 24 hours, 36 and 23% of UVCs (n = 41) migrated into the cardiothymic silhouette, respectively. At 1 and 24 hours, 23 and 11% of PICCs (n = 63) migrated into the cardiothymic silhouette, respectively. Migration was not associated with birth weight, weight at insertion, or postnatal age at insertion.Conclusion UVCs and PICCs frequently migrate into the cardiothymic silhouette increase the risk for development of a pericardial effusion. Serial radiographic assessment of catheter tip location is needed to assess catheter migration within the first 24 hours of line placement.
Keywords: umbilical venous catheter; percutaneously inserted central catheter; pericardial effusion